Living Law in The Perspective of Progressive Law: The Urgency of Its Regulation in The Draft Indonesian Criminal Code - Yusuf Saefudin (Jurnal Dinamika Hukum, 2021)
The discussion on the Indonesian Criminal Code continues and cannot be separated from criticism by various parties. One of the arrangements that has received criticism is regarding living law in society (living law). On the one hand, this regulation emphasizes the existence of living law which is the character of the multi-cultural Indonesian nation. On the other hand, this arrangement is considered to have no legal certainty. This research examines in depth how the urgency of setting living law in the Indonesian criminal law code, as well as examines the existence of this living law in the perspective of progressive law. The research was designed with a normative juridical method. The approach used is a statutory approach and a conceptual approach. The results of the study show that living law arrangements in the criminal law code are very important to provide legal certainty for the existence of indigenous and tribal peoples in Indonesia. Living law arrangements are also in line with the spirit of progressive law enforcement. For law enforcers, especially judges, this arrangement reinforces the provisions of Article 5 paragraph 1 which requires judges to explore, follow and understand legal values and a sense of justice that lives in society.Keywords: Living Law, Progressive Law, Criminal Code